COMPARATIVE EVALUATION OF ANTIOXIDANT ACTIVITY OF SUBSTITUTED FLAVONES - William, Helen; N, Narayanan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The flavonoids are a heterogeneous group of plant polyphenols that are endowed with several biological activities including antioxidant, anti-inflammatory, immunomodulatory, antiviral, antimutagenic, and anticarcinogenic properties. They are believed to interfere with the various free radical-producing systems and they also enhance the functions of endogenous antioxidants. The aim of this study was to compare the antioxidant activity of synthesized substituted flavones by various free radical scavenging assays. Methods: The flavones used in the study, 6,3',4' - trihydroxy flavones (THF) and 3-hydroxy-6,3'-dimethoxy flavones were synthesized using standard procedures and their antioxidant activity was compared by 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, hydrogen peroxide scavenging assay, hydroxyl radical scavenging assay, reducing power capacity, superoxide free radical scavenging assay, and 2,2â€²-azino-bis-3-ethylbenzthiazoline-6- sulphonic acid assay. Results: In the DPPH assay, THF has an inhibitory concentration 50% value of 18.89 Î¼g/ml which was much better than that of standard ascorbic acid which was 26.1 Î¼g/ml. The THF had a much better antioxidant activity in most of the free radical scavenging assays. Conclusion: From the study, it can be seen that the flavones showed significant antioxidant activity that can be used for treatment of various diseases